Primary Vitreoretinal Lymphoma: A Report from an International Primary Central Nervous System Lymphoma Collaborative Group Symposium - Chan, Chi‐Chao; Rubenstein, James L.; Coupland, Sarah E.; Davis, Janet L.; Harbour, J. William; Johnston, Patrick B.; Cassoux, Nathalie; Touitou, Valerie; Smith, Justine R.; Batchelor, Tracy T.; Pulido, Jose S. (The oncologist (Dayton, Ohio), 2011)
Primary vitreoretinal lymphoma (PVRL), also known as primary intraocular lymphoma, is a rare malignancy typically classified as a diffuse large B‐cell lymphoma and most frequently develops in elderly populations. PVRL commonly masquerades as posterior uveitis and has a unique tropism for the retina and central nervous system (CNS). Over 15% of primary CNS lymphoma patients develop intraocular lymphoma, usually occurring in the retina and/or vitreous. Conversely, 65%–90% of PVRL patients develop CNS lymphoma. Consequently, PVRL is often fatal because of ultimate CNS association. Current PVRL animal models are limited and require further development. Typical clinical findings include vitreous cellular infiltration (lymphoma and inflammatory cells) and subretinal tumor infiltration as determined using dilated fundoscopy, fluorescent angiography, and optical coherent tomography. Currently, PVRL is most often diagnosed using both histology to identify lymphoma cells in the vitreous or retina and immunohistochemistry to indicate monoclonality. Additional adjuncts in diagnosing PVRL exist, including elevation of interleukin‐10 levels in ocular fluids and detection of IgH or T‐cell receptor gene rearrangements in malignant cells. The optimal therapy for PVRL is not defined and requires the combined effort of oncologists and ophthalmologists. PVRL is sensitive to radiation therapy and exhibits high responsiveness to intravitreal methotrexate or rituximab. Although systemic chemotherapy alone can result in high response rates in patients with PVRL, there is a high relapse rate. Because of the disease rarity, international, multicenter, collaborative efforts are required to better understand the biology and pathogenesis of PVRL as well as to define both diagnostic markers and optimal therapies. 摘要 原发性玻璃体视网膜淋巴瘤（PVRL），又称原发性眼内淋巴瘤，是一种罕见的恶性肿瘤，通常被归为弥漫性大B细胞淋巴瘤，老年人多见。PVRL仅发生于视网膜和中枢神经系统，常被误认为后色素层炎。超过15%的原发性中枢神经系统淋巴瘤患者发生眼内淋巴瘤，通常发生在视网膜和/或玻璃体。相反，65%~90%的PVRL患者发生中枢神经系统淋巴瘤。由于PVRL最终与中枢神经系统相关联，因此往往是致命的。目前的PVRL动物模型有局限性，需进一步开发。典型临床表现为在散瞳眼底镜检查、荧光血管造影和 光学相干断层扫描 下可见玻璃体细胞浸润（淋巴瘤和炎症细胞）和视网膜下肿瘤浸润。目前，PVRL最常用的诊断方法是通过组织学确定玻璃体或视网膜的淋巴瘤细胞、以及免疫组化提示单克隆性。其他PVRL辅助诊断方法包括眼内液白介素‐10增高、恶性细胞中检测出IgH 或T细胞受体基因重排。PVRL的最佳治疗方案尚未确定，需要肿瘤科医生和眼科医生通力合作。PVRL对放疗敏感，并对玻璃体内注射甲氨蝶呤或利妥昔单抗具有高反应性。虽然PVRL采用全身化疗缓解率较高，但复发率也较高。由于本病罕见，因此需要国际性多中心的协作努力，才能更透彻地了解PVRL的生物学特性和发病机制，确定其诊断标记物和最佳疗法。 A symposium on primary vitreoretinal lymphoma held at the Fifth Annual, National Cancer Institute–sponsored International Primary Central Nervous System Lymphoma Collaborative Group conference, a multidisciplinary meeting, is summarized herein. Tumor biology, nomenclature, epidemiology and prognosis, biology and pathogenesis, animal models, clinical manifestations, diagnosis, therapeutics, and future investigations are reviewed.